2016
DOI: 10.1002/minf.201501029
|View full text |Cite
|
Sign up to set email alerts
|

How to Choose the Suitable Template for Homology Modelling of GPCRs: 5‐HT7 Receptor as a Test Case

Abstract: G protein-coupled receptors (GPCRs) are a super-family of membrane proteins that attract great pharmaceutical interest due to their involvement in almost every physiological activity, including extracellular stimuli, neurotransmission, and hormone regulation. Currently, structural information on many GPCRs is mainly obtained by the techniques of computer modelling in general and by homology modelling in particular. Based on a quantitative analysis of eighteen antagonist-bound, resolved structures of rhodopsin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 72 publications
3
1
0
Order By: Relevance
“…However, it can still be quite high up to 20% sequence identity. These findings are in accordance with previous studies that considered the comparative modeling of G protein-coupled receptors (GPCRs). In Figure , this dependence is also visualized by clustering. In this clustering, the distance between each pair of proteins (say A and B) is higher when the structure building algorithm produces models of target A based on template B and vice versa, of lower quality.…”
Section: Results and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, it can still be quite high up to 20% sequence identity. These findings are in accordance with previous studies that considered the comparative modeling of G protein-coupled receptors (GPCRs). In Figure , this dependence is also visualized by clustering. In this clustering, the distance between each pair of proteins (say A and B) is higher when the structure building algorithm produces models of target A based on template B and vice versa, of lower quality.…”
Section: Results and Discussionsupporting
confidence: 91%
“…On the other hand, we found that models of good quality, especially in the TM region, can be generated even in the 20–40% region of target-template sequence identity. These findings were earlier reported for the homology modeling of GPCRs. …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In efforts to detect novel bioactive ligands, ligand-based techniques, including properties-based and pharmacophore-based tools, are being used more and more for modeling the bioactivity of molecules and for the virtual screening of large chemical databases [ 35 , 36 , 37 , 38 ]. Ligand-based modeling tools use optimization algorithms such as Monte Carlo simulations (MCs), simulated annealing (SA) [ 39 ], genetic algorithms (Gas) [ 40 ], neural networks (NNs) [ 41 ], support vector machines (SVM) [ 42 ], the k-nearest neighbor algorithm (kNN) [ 43 , 44 ], Bayesian classifiers and some combinations thereof (Monte Carlo/ simulated annealing algorithm, MCSA) [ 45 , 46 , 47 , 48 , 49 ]. Distinguishing between active and inactive ligands that are useful for treating a certain disease may be accomplished by using sets of active and inactive chemicals and certain optimization techniques [ 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%